2004
DOI: 10.1016/j.orthres.2003.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit knee model of post‐traumatic joint contractures: The long‐term natural history of motion loss and myofibroblasts

Abstract: Our objective is to describe the natural history of motion loss with time and myofibroblast numbers in a rabbit knee model of post-traumatic joint contractures. Twenty-eight skeletally mature New Zealand White female rabbits had five-mm-squares of cortical bone removed from the medial and lateral femoral condyles of the right knee. A Kirschner wire (K-wire) was used to immobilize the knee joint in maximum flexion. A second operation was performed 8 weeks later to remove the K-wire. The rabbits were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
147
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(160 citation statements)
references
References 43 publications
(15 reference statements)
13
147
0
Order By: Relevance
“…Hildebrand et al 17 have studied the recovery process of post-traumatic contractures with immobilized rabbit knees for 8 weeks followed by remobilization. They have shown that contracture severity decreases with time although it does stabilize in the long term and that processes involved are somewhat altered depending on the underlying etiology of the contracture process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hildebrand et al 17 have studied the recovery process of post-traumatic contractures with immobilized rabbit knees for 8 weeks followed by remobilization. They have shown that contracture severity decreases with time although it does stabilize in the long term and that processes involved are somewhat altered depending on the underlying etiology of the contracture process.…”
Section: Discussionmentioning
confidence: 99%
“…Most information obtained on contracture formation over time is based on animal models with contractures produced by immobilizing joints with internal fixation (with plate or splint), 5,6,[9][10][11] external fixation (with cast, bandage, or splint), [12][13][14] pinning, 15 wiring, 16,17 or a combination of these procedures. Contractures after immobilization mainly result from stress deprivation of joints.…”
Section: Introductionmentioning
confidence: 99%
“…Rabbits in group II (n ¼ 16) were operated on using an identical protocol except for the absence of capsular injury, as described by Hildebrand et al 7 Eight rabbits in each group were sacrificed 8 weeks after the procedure (subgroups IA and IIA). The remaining eight rabbits in each group had their immobilization removed and were allowed free activity in a cage for 16 weeks before being sacrificed (subgroups IB and IIB).…”
Section: Methodsmentioning
confidence: 99%
“…The 16-week remobilization time period was selected based on previous observations of a plateau in spontaneous motion gains after 16 weeks of free cage activity. 7 After prepping and draping the animals in the usual sterile fashion, inhalational general anesthesia was induced with isoflurane (1%-2%). A 15-blade scalpel was used to make a 1-cm longitudinal skin incision over the tibia.…”
Section: Subgroups Ib and Iibmentioning
confidence: 99%
See 1 more Smart Citation